Nothing sacred - Gourgouris, Stathis (Columbia University Press, 2024)
"Enlightenment thought is widely considered to consist of four key features--atheism, democracy, humanism, and modernity. Common to all is an explicit process of desacralization. Yet the intellectual history of these concepts reveals that in the process of desacralization new sacred spaces arose in their name. The aim of Nothing Sacred is to question this second-order sacralization and consider, in a form of negative dialectics, whether (and how) these domains can argue against themselves in order to once again desacralize their own self-sacralization. Secular critique is not simply an attack on religion but rather on the range of society's unavowed self-occlusions. Its object is to elucidate the politics and practices of knowledge that animate them. In the field of religion critique challenges the alleged permanence of political theology and transforms the epistemologies of both sacred and secular. For Stathis Gourgouris the state of nature that he terms political animality critiques political theology much as the anarchy of democracy, inhabited by it, critiques sovereignty. He takes aim at the desacralizing capacity of these historical formations, which produce their own historical conditions for self-sacralization, in order to demonstrate their dynamic subversive power against deeply ensconced conditions of disempowerment and incapacitation and to understand how societies and individuals are driven to self-subversion and self-disempowerment. These forces are alive today in the form of discursive "posts"--posthumanism, postdemocracy, post-truth, postracial--which are just as self-sacralizing. Exposing them is not a nostalgic liberal return to an idealized past but an expansive anarchic ontological affirmation of the political dimensions of human animality on a planetary scale and of a radical politics in which democracy has severed its bind to capitalism. Nothing Sacred thinks across orders, obstacles, and intersectional spaces in a world of warring multipolar oligarchies and psychotic rage"--